EVALUATION OF PROBABILITY MODELS ON INSURANCE CLAIMS IN GHANA - Dadey, E. J.; Ankrah, S. (European Scientific Journal, ESJ, 2014)
This study investigates the probability distributions that best fits the number of insurance claims. In particular, it compares the poisson distribution and the negative binomial distribution models to determine which distribution best fit insurance claim data obtained from two Insurance Companies in Ghana. Data on the number of claims of a funeral policy spanning from year 2006 to 2010 were used for the study. Probability distribution models and the parametric bootstrap methods were employed in analyzing the data collected. The Negative Binomial distribution was found to be superior to the Poisson distribution in fitting the claims data. Also, the result revealed that the estimates obtained by the probability models and that of the parametric bootstrap estimates have no significant difference.